BNT162b2 Messenger RNA Vaccination Did Not Prevent an Outbreak of Severe Acute Respiratory Syndrome Coronavirus 2 Variant 501Y.V2 in an Elderly Nursing Home but Reduced Transmission and Disease Severity. (16th May 2021) - Bailly, Benoit; Guilpain, Luc; Bouiller, Kevin; Chirouze, Catherine; N'Debi, Melissa; Soulier, Alexandre; Demontant, Vanessa; Pawlotsky, Jean-Michel; Rodriguez, Christophe; Fourati, Slim
Abstract: We report an outbreak of severe acute respiratory syndrome coronavirus 2 501Y.V2 in a nursing home. All nonvaccinated residents (5/5) versus half of those vaccinated with BNT162b2 (13/26) were infected. Two of 13 vaccinated versus 4 of 5 nonvaccinated residents presented severe disease. BNT162b2 did not prevent the outbreak, but reduced transmission and disease severity.